Repair of an acute Type A aortic dissection with LVAD patient after failed mitral and tricuspid operation. Issue 4 (4th March 2016) - Schmitto, Jan Dieter; Fleissner, Felix; Hanke, Jasmin; Rojas, Sebastian; Avsar, Murat; Martens, Andreas; Shrestha, Malakh; Haverich, Axel; Strueber, Martin
Key Clinical Message: An acute type A dissection in a patient with a left ventricular assist device was treated by replacement of the ascending aorta and the proximal arch using a prosthesis with a side branch which was connected to the left ventricular assist device outflow branch, greatly simplifying the procedure. Abstract : An acute type A dissection in a patient with a left ventricular assist device was treated by replacement of the ascending aorta and the proximal arch, using a prosthesis with a side branch which was connected to the left ventricular assist device outflow branch, greatly simplifying the procedure.